Development and validation of a facile rapid assessment scale for perinatal venous thromboembolism in puerperium in Chinese women - Xiujuan Chen; Wei Peng; Yan Zhang; Huansheng Zhou; Meng Zhang (BMC, 2023)
Abstract Background It is still urgent and challenge to develop a simple risk assessment scale for venous thromboembolism (VTE) in puerperium in Chinese women. Methods The study, a retrospective case-control study, was conducted in 12 hospitals in different cities in China. A total of 1152 pregnant women were selected, including 384 cases with VTE and 768 cases without VTE. A logistic regression method was conducted to determine the risk factors of VTE. Results Age, BMI before delivery, gestational diabetes mellitus, family history (thrombosis, diabetes, cardiovascular disease), and assisted reproductive technology were independent risk factors (P<0.05). The difference between the high-risk group and the low-risk group was statistically significant(P<0.001) with a sensitivity of 0.578, specificity of 0.756, Yuden index o.334, and area under the ROC curve of 0.878. Conclusions The age (≥ 35 years), BMI before delivery (≥ 30 kg/m2), gestational diabetes mellitus, family history of related diseases and assisted reproductive technology are more likely to cause VTE after full-time delivery. The simple and rapid assessment scale of VTE in women after full-term delivery has perfect discrimination (P < 0.001), which can be applied to predict the risk of VTE in Chinese full-term postpartum women.